Interpretation of morphological descriptors on nanocellulose from oil palm frond fibers under weak acid, strong acid, and enzymatic treatments - Kong, Y.L.; Harun, M.Y.; Leong, M.Y.; Looi, C.Y.; Wong, W.F. (Elsevier, 2023)
Surface properties of the nanocellulose network from oil palm frond fibers have been modeled in this work by using a fractal model namely the generalized Cauchy process (GCP) to investigate the local fiber distribution and their geometrical effect on the loading capacity. Using the GCP model, the performance of the nanocellulose network under different treatment processes is quantified by interpreting the dual-fractal properties, namely power-law scaling in the local growth (variance) and correlation function, with independent scaling parameters. Our observations indicated a strong correlation between the fractal dimension of nanocellulose and the type and concentration of treatment chemicals, underlining its sensitivity to treatment variations. Additionally, we investigated the organization of cellulose nanocrystals within the morphological structure through simulated three-dimensional network topology, offering insights into pore distribution and aggregation formation. Furthermore, we delved into the influence of crosslinking on loading capacity. Our findings demonstrated a significant reduction in loading test result inconsistencies, emphasizing the enhanced stability and reliability of crosslinked nanocellulose. This research also highlighted the controlled release capabilities of crosslinked nanocellulose, positioning it as a promising candidate for tailored applications in sustained delivery systems.